Investigating effect of compatibilizer on polymer blend filament from post-used styrofoam and polyethylene for fused deposition modelling. Issue 1 (1st May 2022) - Chow, H M; Koay, S C; Choo, H L; Chan, M Y; Ong, T K
Abstract: This research produced the filament by blending the recycled polystyrene (rPS) from post-used Styrofoam and low-density polyethylene (LDPE). This study used polystyrene-grafted-maleic anhydride (PS-g-MA) as a compatibilizer to the rPS/LDPE blend. The formulated filaments were printed into specimens using a FDM printer. The visual inspection results showed that the printed specimens displayed better adhesion as the printing temperature and extrusion rate percentage increased. The addition of PS-g-MA also enhanced the adhesion of the printed layers. In terms of tensile properties, adoption of PS-g-MA also significantly improved the tensile strength and tensile modulus of the printed specimens. Furthermore, the addition of PS-g-MA increased the degree of crystallinity but it has shown no significant effect on the melting temperature. In addition, compatibilized rPS/LDPE blend samples possessed higher onset thermal degradation temperatures than the uncompatibilized rPS/LDPE blend sample, where higher onset thermal degradation temperature indicated that the material has better thermal stability. Overall, PS-g-MA was an effective compatibilizer to the immiscible rPS/LDPE blend filament where improvements of overall material properties and print quality can be observed, and especially with 5 wt% of PS-g-MA compatibilizer content, the tensile, thermal properties and print quality were improved the most.